Computed Tomography and Magnetic Resonance Imaging Findings of a Malignant Hepatic Epithelioid Hemangioendothelioma - Soo-heui Baek MD; Jung-Hee Yoon MD, PhD (SAGE Publishing, 2013)
We report the case of a rare solitary small nodular form of malignant hepatic epithelioid hemangioendothelioma in a patient followed by computed tomography and gadoxetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging with histological analysis. This case showed early peripheral septal and nodular enhancement and delayed centripetal enhancing pattern with capsular retraction, mimicking peripheral cholangiocarcinoma, inflammatory pseudotumor, or metastases. The histological and immunohistochemical findings were diagnostic of a malignant hepatic epithelioid hemangioendothelioma.